In the wake of diamond mining : a critical assessment of environmental governance and corporate social responsibility in the Namaqualand coastal region - Blair, Iona (Department of Environmental and Geographical Science, 2014)
This study assesses the social and environmental legacy that is currently being left in the wake of diamond mining along the north west coast of South Africa as a result of almost century of diamond mining. This involves an inquiry into the political, economic and ideological forces that enabled the establishment of the extractive industry, and a critical assessment of the role the industry has come to play in the region.